2020
DOI: 10.1021/acssynbio.0c00203
|View full text |Cite
|
Sign up to set email alerts
|

Display of Self-Peptide on Adeno-Associated Virus Capsid Decreases Phagocytic Uptake in Vitro

Abstract: Adeno-associated virus (AAV) vectors are currently investigated as gene transfer agents for the treatment of a variety of diseases. However, activation of the host immune response upon vector administration limits the use of AAV in the clinical setting. To decrease host detection of AAVs, we tested the CD47-based “don’t-eat-me” signal in the context of the AAV capsid. We genetically incorporated the bioactive region of CD47, named “self-peptide” (SP), onto the surface of the AAV2 capsid. AAV mutants were struc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“… 104 Inspired by the self-peptide (SP), a bioactive region of CD47, that acts as a “don’t-eat-me” signal for macrophages, Robinson et al inserted SP onto the capsid of AAV2 to obtain AAV2 mutants with decreased phagocytic susceptibility in vitro. 105 In another study, after injecting the AAV capsid fused to Tregitopes, the human MHC class II epitopes, CD8+ T in splenocytes of mice displayed reduced responses to AAV capsid. 104 , 106 …”
Section: Capsid Modification Strategymentioning
confidence: 98%
“… 104 Inspired by the self-peptide (SP), a bioactive region of CD47, that acts as a “don’t-eat-me” signal for macrophages, Robinson et al inserted SP onto the capsid of AAV2 to obtain AAV2 mutants with decreased phagocytic susceptibility in vitro. 105 In another study, after injecting the AAV capsid fused to Tregitopes, the human MHC class II epitopes, CD8+ T in splenocytes of mice displayed reduced responses to AAV capsid. 104 , 106 …”
Section: Capsid Modification Strategymentioning
confidence: 98%
“…T on the capsid surface. 246 Bucher and colleagues have recently outlined the important role of extra-viral DNA components in AAV suspensions in activating the innate immune response. Their experiment also indicated that treating AAV suspensions with DNase can reduce or even abolish the innate immune response to AAVs without reducing transduction efficiency.…”
Section: Immune Response To Aavmentioning
confidence: 99%
“…Similar to lentivirus, display of the “Self” peptide on the clinically relevant adeno-associated virus vector (AAV) resulted in reduced phagocytic susceptibility of the AAV in vitro . Because AAVs do not have a membrane envelope, the “Self” peptide was directly introduced into an AAV2 capsid protein and flanked by glycine-serine linkers to ensure capsid stability and minimize viral titer loss.…”
Section: “Self” On Viruses Suppresses Phagocytosis and Enhances Gene ...mentioning
confidence: 99%